2017
DOI: 10.1152/physiolgenomics.00103.2016
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic alterations in the brain of painted turtles (Chrysemys picta) developmentally exposed to bisphenol A or ethinyl estradiol

Abstract: Developmental exposure of turtles and other reptiles to endocrine-disrupting chemicals (EDCs), including bisphenol A (BPA) and ethinyl estradiol (EE), can stimulate partial to full gonadal sex-reversal in males. We have also recently shown that in ovo exposure to either EDC can induce similar sex-dependent behavioral changes typified by improved spatial learning and memory or possibly feminized brain responses. Observed behavioral changes are presumed to be due to BPA- and EE-induced brain transcriptomic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…The detailed analysis of the hypothalamic regions in post‐embryonic developmental stages did not provide evidence for disruption in the numbers of mitotically active progenitors and neurones and it is likely that other brain regions might be affected at cellular levels in the bisphenol‐treated larval zebrafish. Indeed, other studies have shown BPA effects on brain regions others than hypothalamus 128,129 . Thus, further analysis should be performed in multiple brain regions to assess how bisphenols affect the neurobehavioural system.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed analysis of the hypothalamic regions in post‐embryonic developmental stages did not provide evidence for disruption in the numbers of mitotically active progenitors and neurones and it is likely that other brain regions might be affected at cellular levels in the bisphenol‐treated larval zebrafish. Indeed, other studies have shown BPA effects on brain regions others than hypothalamus 128,129 . Thus, further analysis should be performed in multiple brain regions to assess how bisphenols affect the neurobehavioural system.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may suggest that exposure to one of these EDCs disrupts the normal neural pathways that regulate select behaviors. We previously determined that developmental exposure to BPA or EE in painted turtles resulted in significant gene expression changes, especially those associated with mitochondrial and ribosomal protein functions, that correlated with prior performance when tested in an aquatic spatial maze [72]. While such analyses cannot establish causation, they suggested a list of candidate genes that may be vulnerable to early life exposure to BPA or EE and contribute to behavioral changes later-inlife.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol A (BPA), which is made by Phenol and acetone [2], is an industrially important chemical that is used as a raw material in the manufacture of many products such as engineering plastics (e.g., epoxy resins/ polycarbonate plastics), food cans (i.e., lacquer coatings), and dental composites/sealants [3]. Extensive evidence indicates that BPA induces feminization during gonadal ontogeny of fishes [4], reptiles [5], birds [6], and human [7,8], and it is identified as an endocrine disruptor and leads to carcinogenesis [9]. Biology is exposed to ubiquitous BPA Though its hazardous effects, more than 5 million metric tons of BPA was produced in 2011 and was mainly used in East Asia (Korea, China and Japan), and kept increasing year by year [10,11].…”
Section: Introductionmentioning
confidence: 99%